RME model based on ethnomathematics “prol tape” typical of Jember in improving fraction concept understanding of madrasah ibtidaiyah students - Sufraini, Sufraini; Dewanti, Sintha Sih; Anriani, Titi; Budi, Tegar Setia; Isnaini, Safira Wahyu (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: This research stems from the problem of learning mathematics, which is still considered scary and difficult. Less varied learning methods make this learning boring for students. Through the development of this Realistic Mathematics Education (RME) learning model based on Jember's typical prol tape ethnomathematics, students enjoy learning more.Aim: This research aims to develop an RME learning model based on ethnomathematics